STRATEGI PEMERINTAH DAERAH DALAM MENGEMBANGKAN PARIWISATA DI KABUPATEN SUMENEP DENGAN METODE FORCE FIELD ANALYSIS - Moh. Romzi; Nur Inna Alfiyah; Rillia Aisyah Haris; Dwi Listia Rika Tini; Enza Resdiana (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
The tourism industry must continue to be the center of attention for both the central and local governments. Sumenep Regency has great tourism potential, including nature tourism, historical tourism, religious tourism and cultural tourism. The development of tourism in Sumenep Regency is regulated in the Regional Regulation concerning RIPPARKAB Number 4 of 2018. The selection of a good and planned strategy will produce a final result that is directed and in accordance with the initial tourism development plan. The strategy carried out by the Sumenep Regency Government needs to be evaluated annually. This research method uses a qualitative method with the Force Field Analysis approach. Data collection uses observation, interview and documentation methods. The purpose of this study was to identify and analyze the inhibiting and driving factors of tourism development strategies in Sumenep Regency. The results of the study showed that there were a number of driving factors, namely; 1) Economic opportunities, 2) Potential uniqueness of tourism, 3) Location access. Inhibiting factors: 1) Promotion, 2) Facilities and infrastructure, 3) Government support, 4) HRD. The results of the analysis showed that the key factor driving tourism development was ease of road access, while the key factor inhibiting tourism was lack of government support. Improvement of strategies in tourism development in Sumenep Regency, namely digital marketing campaigns, provision of innovative, informative and easily accessible websites or social media, improvement of services, tourism experiences and efficient tourism operations and evaluation of accessibility information structures, development of sustainable tourism based on community welfare, improvement and adjustment of accessible tourism facilities, environmental conservation and tourist education, collaboration with local communities, increasing strategic partnerships, improving human resources regarding service inclusiveness, leadership development, and management